Comparing between spiritual well being of patients from the cardiovascular nursing program with individuals who are apparently healthy (2010)
Objective: the study describes and compares the levels of spiritual well-being of the group of patients from the cardiovascular nursing program with those of the group of people with similar socio-demographic characteristics and who are apparently healthy. Methods: a quantitative approached was used of the des-criptive comparative type to measure the spiritual well-being which included the 43 people of the cardiovascular nursing program for the prevention of risk factors and 43 people with similar characteristics and who are apparently healthy. Results: they include the description of spiritual well-being of each one of the groups (people who attend the cardiovascular nursing program and individuals who are apparently healthy) and the comparison between them. An average level of spiritual well-being among the cardiovascular nursing program individuals was found, and it was more committed in the existential dimension than in the religious one. In people who are apparently healthy, the general spiritual well-being level was high, with better results in the religious dimension than in the existential one. When comparing the levels of spiritual well-being in general and by the components, a significant difference was found between the groups with higher levels of spiritual well-being in general and by the components in the group of individuals who are apparently healthy. Discussion: The findings confirm the existence of a link between spirituality and cardiovascular health. The importance of an integral evaluation is emphasized and that should enable the understanding of the dynamics between the different life aspects of people with cardiovascular risk during the cardiovascular nursing program. The importance of including information on spiritual belief and practices is highlighted as a possible protecting factor in the cardiovascular health of people and a debate is open on the strategies to address the dimension of spiritual care and go beyond the theory of the facts in reference to the integrity in a care that is based on health as an expanded conscience.